Internalization of Religious Attitudes Students Through Islamic Education Based on Deep Learning at SMK Negeri 2 Temanggung - syifa salfaira; Luluk Ifadah; Abdul Wahab Fahrub (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Islamic Religious Education is not only intended to improve students’ religious understanding but also to internalize religious values in their daily lives. However, Islamic Education instruction often emphasizes cognitive aspects, resulting in students’ religious knowledge not being fully reflected in their religious attitudes and behavior. This study aims to analyze the implementation of the deep learning approach in Islamic Religious Education and to examine the process of internalizing students’ religious attitudes at SMK Negeri 2 Temanggung. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation. The findings reveal that the implementation of the deep learning approach is carried out through the integration of three core principles: mindful learning, meaningful learning, and joyful learning, which encourage active student engagement, deeper understanding, and meaningful learning experiences. The process of internalizing religious attitudes occurs through three stages: value transformation, value transaction, and value transinternalization. The implementation of the deep learning approach contributes to the development of students’ religious awareness, honesty, responsibility, and respect toward teachers and peers. Therefore, the deep learning approach has significant potential as an effective instructional strategy in Islamic Religious Education for strengthening the internalization of religious values and character development in vocational education settings.